The Effectiveness of Group Guidance with Modeling Techniques on Student Learning Independence - Nafisha, Jihanda; Arsini, Yenti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to determine the effectiveness of group guidance with modeling techniques in increasing student learning independence. This quantitative research with a one-group pre-test-post-test pre-experimental design aims to determine the effectiveness of group guidance with modeling techniques in improving the learning independence of students in grade XI MAS Plus Al-Ulum Medan. Data was obtained from a learning independence questionnaire, with a sample of 12 students selected using the purposive sampling technique. The data collection technique was carried out through pre-test and post-test, which was then analyzed using the Wilcoxon test. The results showed that group guidance with modeling techniques was effective in increasing students' learning independence, with a significance value of 0.002. This increase can be seen from the average pre-test score of 73.58 (low-medium) to 98.83 (medium-high) in the post-test. It is proven that group guidance with modeling techniques is an effective method to increase student learning independence.